2013
DOI: 10.4172/2155-9821.1000141
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Novel Rhenium Compounds on Lymphosarcoma, PC-3 Prostate and Myeloid Leukemia Cancer Cell Lines and an Investigation on the DNA Binding Properties of One of these Compounds through Electronic Spectroscopy

Abstract: Despite the tremendous success of cisplatin and other platinum-based anticancer drugs, severe toxicity and resistance to tumors limit their applications. It is believed that the coordination (formation of covalent bond) of the metal (platinum) to the nitrogen bases of DNA cause the ruptures of the cancer as well as normal cells. A search for anticancer drugs with different modes of action resulted in the synthesis of variety of novel compounds. Many of them are in clinical trials now. Recently we synthesized a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The studies show that they interact with DNA via partial insertion, and the anticancer activity is the same as the DNA-binding activity, which increases with the lipophilicity of the complexes. The Re atoms of the Re complexes Re-16a [ 96 ] and Re-17a [ 97 ] ( Figure 2 ) coordinate with three planar carbonyl and planar polypyridine aromatic ligands to form an octahedral structure. Because of the planarity of aromatic phenanthroline rings, the complexes are forced to insert into the DNA bases.…”
Section: Study On Re In Cancer Therapymentioning
confidence: 99%
“…The studies show that they interact with DNA via partial insertion, and the anticancer activity is the same as the DNA-binding activity, which increases with the lipophilicity of the complexes. The Re atoms of the Re complexes Re-16a [ 96 ] and Re-17a [ 97 ] ( Figure 2 ) coordinate with three planar carbonyl and planar polypyridine aromatic ligands to form an octahedral structure. Because of the planarity of aromatic phenanthroline rings, the complexes are forced to insert into the DNA bases.…”
Section: Study On Re In Cancer Therapymentioning
confidence: 99%
“…The other alternative complexes have at least one direct, covalent metal-carbon bond, having structural variety, diverse stereochemistry, provide control over major kinetic properties, kinetically stable, usually uncharged, and having low oxidation state of metal atom, so they can be used as ideal candidates for anticancer candidates [1][2][3][4]. Some examples are: metallocenes [5][6][7][8][9], organometallic ruthenium half-sandwich complexes [10][11][12][13][14], organometallic osmium half-sandwich complexes [15][16][17], organometallic iridium and rhodium complexes [18][19][20][21], rhenium organometallics [22][23][24], ruthenium, osmium, iridium, and platinum organometallics as scaffolds for protein kinase inhibitors, metal NHC complexes [25,26], and metal carbonyl complexes [27,28].…”
Section: Anticancer Agentsmentioning
confidence: 99%
“…The remedy is now to search for new compounds with new mode of action to overcome the resistant strains. This can be done by either the organic derivatization of old drugs or completely new organometallic drugs, for example, new tamoxifen [19][20][21]29], platensimycin [22][23][24], etc.…”
Section: Antibacterial Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the exploration of the [2 + 1] strategy for the design of new Re(I) complexes by using the appropriate ligands, there is an increased interest on the study of intermolecular interactions of Re(I) complexes in the solid state [ 33 35 ] based on diverse types of interactions of rhenium complexes with DNA [ 36 , 37 ]. Similar systematic crystal structure studies [ 38 40 ] have revealed the importance of lone pair π and more specifically the role of carbonyl-carbonyl interactions on the supramolecular assembly of Re complexes.…”
Section: Introductionmentioning
confidence: 99%